'Training the trainers' of teachers in France: assessment and outlook - Lapostolle, Guy [Verfasser] (My University, 2009)
"With the creation of IUFMs (university institutes of teacher training) in the 1990s, the training of teacher trainers in France has become a fundamental part of the renewal of teacher training. It is seen as a fundamental lever for the IUFMs to achieve the tasks and goals entrusted to them: training teachers who need to accommodate the new demands of their profession. To do this, the IUFMs have established 'trainer training programmes'. A closer look at these programmes reveals that a professionalisation of trainers has begun which is giving the IUFMs a stronger role in working towards achieving the goals set. However, some current reforms seem to be questioning the future of this professionalisation and, beyond that, the place and role that the IUFMs will play both in training teachers as well as in the universities in which they have just been integrated." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; I 2.2.1 Westeuropa; Bildungspersonal; Lehrerausbildung; Professionalisierung; Frankreich